EFEKTIFITAS VOID DAN TAMAN INTERIOR PADA KENYAMANAN TERMAL DI DALAM RUANG - Hakim, Luqmanul; Gunawan, Andi; Sulistyantara, Bambang (Jurnal Lanskap Indonesia, 2016)
ABSTRACTComfort in a place is a dream shared by all people while doing all kinds of activities, consequently all the factors that promote comfort activity will be attempted to be met, such as sufficient space, adequate facilities, adequate lighting, comfortable aeration, safety, beauty, self-esteem and so forth.The concern of this study is how comfort can be achieved by combining natural factors with environmental factors such as plant-made form void (vertical openings) in the design of a simple house. Combination of the two factors is expected to increase comfort in the simple house, that is a change in thermal comfort factors such as the flow of wind speed, air humidity and air temperature in the room. The study was conducted as utilizing experimental method (experimental), is that creating two (2) rooms of the same size but with different treatment, one room (a) with voids and one other room (b) without voids.This study found that, 1). the existence of voids in a room are very significant in improving thermal comfort of the room, 2). the existence of plants as an element of the interior garden are less significant in improving thermal comfort of the room 3). the interaction between the void and garden does not make a significant contribution in improvingthe thermal comfort of the room. Provision of void in a room will increase the speed of air flow.This study provides voids and garden design solutions that can provide the convenience factor, especially the aeration of space by minimizing the use of artificial energy such as electricity and maximize the use of natural resources.